Do Financial Performance and Company Characteristics Affect Corporate Social Responsibility (CSR) Disclosure? - Siswanto, Ely; Daniswara, Daffa Ramamilendra (Adpebi International Journal of Multidisciplinary Sciences, 2022)
Purpose – The purpose of this study was to know the influence of leverage, company size, company age, board of commissioners, and liquidity on corporate disclosure of Corporate Social Responsibility (CSR) in energy companies listed on the Indonesia Stock Exchange. Methodology/approach – We used quantitative methods in this study. The population in this study is energy companies listed on the Indonesia Stock Exchange from 2017-2019. The samples in this study were 50 companies obtained by purposive sampling methods. Data is collected through secondary data documentation sourced from the official website of the Indonesia Stock Exchange. This study used the multiple regression method. Findings – The conclusions from the present study are : a) leverage, liquidity and board of commissioners has no effect on CSR disclosure; 2) firm size and firm age has a positive and significant effect on CSR disclosure. Novelty/value –  CSR in the energy sector is still an interesting theme for the case in Indonesia